Developing countries and the next round of multilateral trade negotiations. - KRUEGER, Anne (1999)
Considers the interests of the developing countries in the next round of multilateral trade negotiations. Examines the issues in which virtually all developing countries have similar interests, and those questions which are significant to major groups of developing countries. Considers the various issues that may arise in future investigations and attempts to assess the developing countries interest in them.